2021
DOI: 10.1038/s41598-021-89902-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered mapping of sound frequency to cochlear place in ears with endolymphatic hydrops provide insight into the pitch anomaly of diplacusis

Abstract: A fundamental property of mammalian hearing is the conversion of sound pressure into a frequency-specific place of maximum vibration along the cochlear length, thereby creating a tonotopic map. The tonotopic map makes possible systematic frequency tuning across auditory-nerve fibers, which enables the brain to use pitch to separate sounds from different environmental sources and process the speech and music that connects us to people and the world. Sometimes a tone has a different pitch in the left and right e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…ANOW thresholds in Figure 2B are consistent with those made previously showing that ANOW thresholds relate to low-characteristic frequency auditory nerve fiber firing thresholds as well as CAPs relate to high-characteristic frequency auditory nerve fiber firing threshold (Lichtenhan et al 2013). Moreover, the before-implantation audiometric configuration is similar to what we have reported previously (Lee et al 2020;Valenzuela et al 2020a, b;Guinan et al 2021;Lefler et al 2021).…”
Section: Acute Hearing Loss Resulted From Cochlear Implantationsupporting
confidence: 91%
See 1 more Smart Citation
“…ANOW thresholds in Figure 2B are consistent with those made previously showing that ANOW thresholds relate to low-characteristic frequency auditory nerve fiber firing thresholds as well as CAPs relate to high-characteristic frequency auditory nerve fiber firing threshold (Lichtenhan et al 2013). Moreover, the before-implantation audiometric configuration is similar to what we have reported previously (Lee et al 2020;Valenzuela et al 2020a, b;Guinan et al 2021;Lefler et al 2021).…”
Section: Acute Hearing Loss Resulted From Cochlear Implantationsupporting
confidence: 91%
“…CAP tone-bursts audiograms of naive (i.e., non-implanted) guinea pigs are most sensitive (i.e., had the lowest thresholds) at 8 to 11 kHz and are less sensitive elsewhere (Fig. 1B; Lee et al 2019, 2020; Valenzuela et al 2020a, b; Guinan et al 2021; Lefler et al 2021). While the threshold of audibility is essentially “U-shaped,” the initial cochlear implant insertion elevated 3 to 11 kHz thresholds and the audiograms became “W-shaped” and were indicative of dysfunction in mid-frequency tonotopic cochlear regions where the implant was in place (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our observation of shortened SFOAE delays (Fig. 7; 40 dB FPL) may appear to conflict with the notion—recently supported by measurements of the cochlear frequency map in guinea pigs with induced hydrops (Guinan et al 2021)—that a stiffened cochlear partition in hydropic ears will shift the peak of the traveling wave toward the apex. If SFOAE delays were determined primarily by the round-trip distance between the stapes and the peak of the traveling wave, then an apically shifted peak would produce longer delays.…”
Section: Discussioncontrasting
confidence: 81%
“…In the EH ear, excessive fluid in the scala media can press on the basilar membrane thereby stiffening it and causing an altered frequency‐position map of the cochlea and the operating point of OHC transfer function. 13 , 14 , 28 , 29 , 30 , 31 In the apical turn of the cochlea, where compliance of the basilar membrane is highest, source deflection might occur, resulting in a phase change in DPOAEs. 32 It has previously been reported that unstable operating points likely affect the phase rather than the amplitude of DPOAEs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there were frequency ranges where the EH ear showed improved SNR and also significant DPOAE responses. In the EH ear, excessive fluid in the scala media can press on the basilar membrane thereby stiffening it and causing an altered frequency‐position map of the cochlea and the operating point of OHC transfer function 13,14,28–31 . In the apical turn of the cochlea, where compliance of the basilar membrane is highest, source deflection might occur, resulting in a phase change in DPOAEs 32 .…”
Section: Discussionmentioning
confidence: 99%